Konjac glucomannan-based nanogel and preparation method thereof, polyphenol nanogel
Through the ionic cross-linking method of acylated chitosan and carboxymethyl konjac glucomanan, the preparation difficulty of konjac glucomanan in the preparation of nanoparticles was solved, and nanogels with excellent encapsulation ability were prepared. Expand its application potential in the fields of drug delivery and food science.
Patent Information
- Application Number
- CN202410920227.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-07-10
AI Technical Summary
The existing konjac glucomannan faces huge molecular weight, high viscosity and neutral charge problems in the preparation of nanoparticles, which lead to difficulties in preparation.
Chitosan acylated chitosan is prepared by reacting citric acid and sodium hypophosphite with chitosan under oil bath conditions, and konjac glucomannan is subjected to hydrogen peroxide-assisted irradiation degradation, alkalization and etherification treatment to obtain carboxylic Methyl konjac glucomanan, and then konjac glucomanan-based nanogel was prepared by ionic cross-linking.
Successfully prepared konjac glucomannan-based nanogel with small particle size, uniform distribution, not easy to aggregation and high yield. It has excellent polyphenol encapsulation and loading capacity, and is suitable for drug delivery, biomedical and food science fields. .
Smart Images

Figure CN118725349B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material technology, and in particular relates to a konjac glucomannan-based nanogel and a preparation method thereof, and a polyphenol nanogel. Background Art
[0002] Nanogel is a gel material with nanoscale structural features, unique swelling and elastic properties, and has broad application prospects in drug delivery, biomedicine, and food science. Its good biocompatibility, large surface area, and pore structure enable it to effectively load hydrophilic or hydrophobic components, increase stability and bioavailability; by regulating the chemical composition and physical properties of the gel, it can achieve slow, continuous, or responsive release of functional ingredients. In addition, nanogel as a carrier can reduce the perception of special odors or tastes in food, improve the overall food quality, and simultaneously embed multiple nutrients to provide more comprehensive nutrition.
[0003] There are various methods for preparing polysaccharide-based nanogels. The multifunctional groups on the polysaccharide skeleton can be easily modified by chemical or biochemical methods to synthesize polysaccharide-based nanoparticles with diverse structures to meet the needs of different application fields. As the only natural cationic polysaccharide, chitosan has been widely reported in the field of nanoparticle materials. For example, chitosan oligosaccharide / alginate nanoparticles can be used as an effective carrier for astaxanthin, improving the stability, in vitro oral bioaccessibility and bioavailability of astaxanthin. In contrast, there are relatively few literatures on konjac glucomannan-based nanoparticles. The large molecular weight, high viscosity and neutral charge make konjac glucomannan face some challenges in the preparation of nanoparticles. Modification and degradation are the current focuses of exploration. Summary of the invention
[0004] The purpose of the embodiments of the present application is to provide a konjac glucomannan-based nanogel to solve the problems of large molecular weight, high viscosity and neutral charge faced by existing konjac glucomannan in the preparation of nanoparticles.
[0005] The embodiment of the present application is achieved by a method for preparing a konjac glucomannan-based nanogel, characterized in that it comprises:
[0006] After dissolving citric acid and sodium hypophosphite in water, chitosan is added and reacted in an oil bath at 110-120° C. to obtain acylated chitosan;
[0007] The konjac glucomannan is dissolved in a hydrogen peroxide solution and then subjected to irradiation degradation treatment;
[0008] The konjac glucomannan treated by irradiation degradation is alkalized, and then chloroacetic acid is added for etherification to obtain carboxymethyl konjac glucomannan.
[0009] The carboxymethyl konjac glucomannan is swollen in a buffer solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added and mixed, and then the acylated chitosan is added dropwise under stirring to react, so as to obtain a konjac glucomannan-based nanogel; the mass ratio of the carboxymethyl konjac glucomannan to the acylated chitosan is 1:(0.5-2).
[0010] The embodiment of the present application also provides a konjac glucomannan-based nanogel, and the konjac glucomannan-based nanogel is prepared by the above-mentioned preparation method of the konjac glucomannan-based nanogel.
[0011] The embodiment of the present application also provides a polyphenol nanogel, which is prepared from the above-mentioned carboxymethyl konjac glucomannan, the above-mentioned acylated chitosan and polyphenol;
[0012] Wherein, the mass ratio of the carboxymethyl konjac glucomannan to the acylated chitosan is 1:(0.5-2); the mass ratio of the polyphenol to the acylated chitosan is (0.5-1):1.
[0013] The present application embodiment provides a method for preparing a konjac glucomannan-based nanogel, wherein citric acid, sodium hypophosphite, and chitosan are placed in an oil bath reaction at 110-120°C, and konjac glucomannan is subjected to hydrogen peroxide-assisted irradiation degradation, alkalization, and etherification treatment, and acylated chitosan and carboxymethyl konjac glucomannan with concentrated molecular weight distribution, small PDI index, and low molecular weight are successfully prepared, and then two acylated chitosans with opposite charges and carboxymethyl konjac glucomannan are ionically cross-linked according to a specific mass ratio, and the obtained konjac glucomannan-based nanogel has a small particle size, uniform distribution, is not easy to aggregate, and has a high yield, and has excellent polyphenol encapsulation and loading capacity. This application provides an important reference for the optimization and application expansion of the preparation process of polysaccharide-based nanogels. Future research will focus on exploring the drug release behavior, biocompatibility, and targeted delivery applications of nanogels to further improve their efficacy and application potential in the fields of drug delivery, biomedicine, and food science. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The water solubility results (A and B), gel permeation chromatogram (C) and molecular weight distribution diagram (D) of chitosan and acylated chitosan provided in the examples of the present application;
[0015] Figure 2 The infrared spectrum (A) and nuclear magnetic resonance (NMR) of chitosan and acylated chitosan provided in the examples of the present application 1 H spectrum (B) and 13 C spectrum (C);
[0016] Figure 3 Gel permeation chromatography (A) and molecular weight distribution diagram (B) of degradation products of KGM at different irradiation doses provided in the examples of the present application;
[0017] Figure 4 The infrared spectrum of the degradation products of KGM at different irradiation doses provided in the examples of the present application (A), the infrared spectrum of CKGM6 (B), the nuclear magnetic resonance (NMR) of KGM6 and CKGM6 1 H spectrum (C) and 13 C spectrum (D);
[0018] Figure 5 The particle size (A), picture (B), yield (C), UV full wavelength scanning spectrum (D) and scanning electron microscope image (E) of the nanogel provided in the examples of the present application.
[0019] Figure 6 This is a technical diagram for preparing konjac glucomannan-based nanogels provided in the examples of the present application. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0021] The present invention provides a method for preparing a konjac glucomannan-based nanogel, comprising the following steps:
[0022] Step S1: After dissolving citric acid and sodium hypophosphite in water, chitosan is added and reacted in an oil bath at 110-120° C. to obtain acylated chitosan (ACs).
[0023] Among them, the viscosity of the chitosan is preferably 5-100 mPa·s. In the embodiment of the present application, acylated chitosan is prepared by using chitosans with different viscosities. It is determined through test characterization that the acylated chitosan obtained by using chitosan with a viscosity of 5-100 mPa·s as a raw material under the oil bath condition at this temperature has a more concentrated molecular weight distribution and a relatively small PDI index, which is helpful to obtain a more uniform and stable nanogel.
[0024] It is worth noting that the 110-120°C oil bath treatment is the key technical point to obtain acylated chitosan with a weight average molecular weight of 2500-2800Da. If the oil bath temperature is lower than 110°C or higher than 120°C, or other drying oven heating methods are used, the molecular weight of the obtained acylated chitosan will be as high as 50,000Da or more.
[0025] Optionally, citric acid and sodium hypophosphite are placed in a pressure-resistant bottle, pure water is added to dissolve them, and then chitosan is added respectively; the reaction is carried out in an oil bath at 110-120° C. with magnetic stirring for 3 h; after the reaction, anhydrous ethanol is added until no precipitation is formed; the precipitate is collected and vacuum freeze-dried for 24 h, taken out, weighed, ground and pulverized to obtain acylated chitosan.
[0026] Step S2: dissolving konjac glucomannan (KGM) in a hydrogen peroxide solution and then subjecting it to irradiation degradation treatment.
[0027] Wherein, in the irradiation degradation treatment, the irradiation dose is preferably 6-10 kGy. The present application embodiment adopts different irradiation doses to carry out irradiation degradation treatment, and the results show that with the increase of irradiation dose, the molecular weight and polydispersity of KGM both show a downward trend. However, under high-dose irradiation, the molecular weight distribution is more uniform, which is conducive to the preparation of nanoparticles in the next step.
[0028] Optionally, KGM powder is dissolved in a 1% hydrogen peroxide solution, mixed and irradiated (60Co, Guizhou Jinnong Irradiation Technology Co., Ltd.), then concentrated by rotary evaporation until viscous, washed with anhydrous ethanol, precipitated, and freeze-dried.
[0029] Step S3: alkalizing the konjac glucomannan after the irradiation degradation treatment, and then adding chloroacetic acid for etherification treatment to obtain carboxymethyl konjac glucomannan (CKGM).
[0030] The mass ratio of chloroacetic acid to konjac glucomannan is preferably (0.75-1.5): 1, more preferably 0.75: 1. By controlling the mass ratio of chloroacetic acid to konjac glucomannan, it is beneficial to obtain carboxymethyl konjac glucomannan with concentrated molecular weight distribution, small PDI index and low molecular weight.
[0031] The weight average molecular weight of the obtained carboxymethyl konjac glucomannan is 3000-8500Da. It is worth noting that the molecular weight control of acylated chitosan and carboxymethyl konjac glucomannan is a crucial factor in the nanogel formation process, which directly affects the particle size of the nanogel.
[0032] Optionally, the lyophilized KGM is placed in a 70% ethanol solution, adjusted to pH 11 using a 1.0 mol / L NaOH solution, and alkalized for 2 hours. After alkalization, chloroacetic acid is added, and the etherification treatment is performed at 50°C (water bath) for 3 hours with magnetic stirring, and then the pH is adjusted to 7.0 using a 1.0 mol / L NaOH solution. The resulting product is precipitated with a 70% ethanol aqueous solution and washed with a 95% ethanol aqueous solution until no residual chloride is detected in the filtrate, and the precipitate is collected and dried at 50°C until the weight is constant, thereby obtaining carboxymethyl konjac glucomannan.
[0033] Step S4: the carboxymethyl konjac glucomannan is swollen in a buffer solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) are added and mixed, and then the acylated chitosan is added dropwise under stirring to react, thereby obtaining konjac glucomannan-based nanogel.
[0034] The mass ratio of carboxymethyl konjac glucomannan to acylated chitosan is preferably 1: (0.5-2), more preferably 1: 1. By controlling the mass ratio of carboxymethyl konjac glucomannan to acylated chitosan, it is advantageous to obtain konjac glucomannan-based nanogel with small particle size, uniform distribution, low aggregation and high yield.
[0035] Alternatively, a certain amount of CKGM was dissolved in morpholineethanesulfonic acid (MES) buffer (pH 5.5) and ensured to be fully swollen to prepare a 10 mg / mL CKGM solution. EDC and NHS were added to the CKGM solution at 10 mmol / L and mixed. Then, a 10 mg / mL ACs aqueous solution was prepared (magnetic stirring was used to completely dissolve it). Finally, ACs was added dropwise to CKGM under magnetic stirring (200 rpm) for 1 h.
[0036] The present application also provides a konjac glucomannan-based nanogel, which is prepared by the above-mentioned konjac glucomannan-based nanogel preparation method. It is worth noting that the present application successfully overcomes the challenges of large molecular weight, high viscosity and neutral charge faced by konjac glucomannan in the preparation of nanoparticles through process optimization, and the prepared konjac glucomannan-based nanogel has great efficacy and application potential in the fields of drug delivery, biomedicine and food science.
[0037] The embodiment of the present application also provides a polyphenol nanogel, which is prepared from the above-mentioned carboxymethyl konjac glucomannan, the above-mentioned acylated chitosan and polyphenol; wherein the mass ratio of the carboxymethyl konjac glucomannan to the acylated chitosan is 1:(0.5-2); the mass ratio of the polyphenol to the acylated chitosan is (0.5-1):1.
[0038] Optionally, the polyphenol nanogel is obtained by swelling the carboxymethyl konjac glucomannan in a buffer solution, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to mix well, and then dropwise adding the mixture of polyphenol and the acylated chitosan under stirring to react.
[0039] Optionally, the polyphenols may be roxburghii polyphenols (RP), grape polyphenols, cocoa polyphenols, onion polyphenols, mung bean polyphenols, etc. Although the present application embodiment only uses RP as an example to prepare polyphenol nanogels, this should not limit the scope of protection of the present application. In addition, the RP used in the present application embodiment can be extracted by existing conventional methods.
[0040] Specific examples of the implementation methods of the present application are given below, which are not intended to limit the scope of the present application.
[0041] In addition, it should be noted that the numerical values given in the following examples are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value.
[0042] Example 1: Preparation of acylated chitosan (ACs):
[0043] Take 11.25g of citric acid and 0.5673g of sodium hypophosphite in a 150mL pressure bottle, add 90mL of pure water to dissolve, and then add 4.5g of chitosan with different viscosities respectively: H Cs (200-600mPa·s), M Cs (20-100mPa·s), L Cs (5-20 mPa·s) and O Cs; 110℃ oil bath 110-120℃ magnetic stirring reaction for 3h; after the reaction, add anhydrous ethanol until no precipitation occurs; collect the precipitate and freeze-dry it in vacuum for 24h, take it out, weigh it, grind it, and the obtained acylated chitosan is named H ACs, M ACs, L Acs and O ACs.
[0044] The present invention investigates the water solubility and molecular weight of several chitosans and their acylated products. Figure 2 As shown. Chitosan is a chain macromolecule formed by glucose units connected by β-1-4 glycosidic bonds. Due to the electrostatic attraction between the cationic glucosamine units in the chitosan molecule, the chitosan molecules form a tight aggregate in water, which limits the penetration of water molecules. At the same time, the larger molecular weight of chitosan increases the intermolecular van der Waals force, making it difficult to form a sufficient hydration layer in water, and thus difficult to disperse and dissolve in water. After acylation modification, hydrophilic carbonyl groups are introduced into the molecules, the intermolecular steric hindrance increases, the original intermolecular and intramolecular hydrogen bonds are destroyed, and the crystallinity of the molecules is further reduced, making the acylated chitosan easier to form hydrogen bonds with water, thereby significantly improving the water solubility.
[0045] The results of the present application show that ( Figure 2 A and 2B), H Cs, M Cs, and L Cs is insoluble in water, O Both Cs and ACs groups are soluble in water. H Cs has the highest viscosity, and its acylation product ( H The water solubility of ACs is still 80%, which is much higher than that of unmodified chitosan. Chitosan oligosaccharides are composed of only a few glucose units, with a low degree of polymerization (DP < 50-55) and molecular weight (Mw < 10kDa). They are easy to form a hydration layer in water, and their hydroxyl (-OH) functional groups are hydrophilic and have high solubility in water. In addition, it was observed that O The color of ACs solution is dark brown, which may be due to the high reaction temperature causing the oligosaccharide molecules to dehydrate, crack, condense, etc., to generate colored organic compounds such as aldehydes and ketones. O ACs and CKGM could not form nanogels.
[0046] The water solubility of acylated chitosan is also related to the lower molecular weight. As shown in Table 1, M ACs, L ACs, H AC and O The weight average molecular weight (Mw) and viscosity average molecular weight (Mz) of ACs are arranged in descending order, while the PDI index is arranged in the opposite order. Figure 2 C and 2D show the GPC spectrum and molecular weight distribution results, respectively. M ACs and L The molecular weight distribution of ACs is more concentrated and the PDI index is smaller. O ACs and H The molecular weight distribution of ACs is relatively broad, especially O The polydispersity index of ACs was the largest, reaching 13.13.
[0047] Table 1
[0048] Acylated chitosan Mn(Da) Mw(Da) Mz(Da) PDI(Mw / Mn) <![CDATA[ H ACS]]> 365 1951 2872 5.35 <![CDATA[ M ACS]]> 1677 2744 6462 1.42 <![CDATA[ L ACS]]> 1771 2518 4300 1.64 <![CDATA[ O ACs]]> 96 1265 2857 13.18
[0049] Considering that the molecular weight of polysaccharides directly affects the size of the nanogel particles formed, and the width of the molecular weight distribution will affect the uniformity and stability of the particles. Based on the observation results, it is determined M ACs and L ACs are more suitable as materials for the preparation of nanogels because they have a more concentrated molecular weight distribution and a relatively small PDI index. These characteristics may help to obtain more uniform and stable nanogels.
[0050] Figure 3 A shows the chitosan group ( H Cs, M Cs, L Cs and O Cs) and acylated chitosan group ( H ACs, M ACs, L ACs and O The infrared spectrum characteristic peaks of ACs) are shown in Figure 2. The two groups of samples have a peak at 3360 cm -1 The broad peak at 3284 cm represents the intermolecular and intramolecular hydrogen bonds of hydroxyl (-OH). After acylation modification, the intermolecular hydrogen bonds weaken, resulting in the weakening of this peak in acylated chitosan. -1 The absorption peak at 1720cm reflects the stretching vibration of primary amine (-NH2) or secondary amine (-NH). -1 The new absorption peak indicates the vibration of the carbonyl group (-C=O) introduced by acylation, which comes from the acylation reaction between citric acid and -NH2 in chitosan; COO - The absorption intensity of the groups is ranked as follows: H ACs<ACOS< L ACs< M ACs, which is positively correlated with the degree of substitution of acylated chitosan. Other characteristic peaks include 1384 cm -1 CN bond vibration, 1069cm -1 The CO bond vibration, and 1022cm -1 The alkyl skeleton vibration of chitosan. -1 and 1588cm -1 The characteristic peaks of COS and ACOS appear at 1617cm -1 and 1511cm -1 , which are the absorption peaks of aldehydes, ketones, etc.
[0051] L Liquids for ACs 1 H and spectrum 13 C( Figure 3B and 3C) show that multiple NMR absorption peaks at 3≤δ≤7ppm are absorption peaks of H atoms in the main chain of acylated chitosan. The chemical shifts of the 6 H atomic absorption peaks in the molecular skeleton are H1 (δ4.89), H3 (δ3.92), H5 (δ3.79), H4 (3.74), H6 (δ3.59), H2 (δ3.19), and the peak observed at δ2.07 corresponds to the NH2 group of glucosamine (GlcN). In the range of 2.85-2.69ppm, the CH2 group produced by the acylation reaction of chitosan with citric acid was observed, δ7.39 corresponds to the amide bond (-CO-NH-), and the peak observed at 6.62ppm corresponds to the OH group of -CC(O)CO.
[0052] Similarly, the absorption peak of the C skeleton of glucosamine is distributed between 60-110ppm, and the chemical shifts are C1 (δ101.44), C6 (δ60.54), C2 (δ55.00), C5 (δ76.79), C3δ (73.87), C4δ (70.15). It is worth noting that δ97.66 and δ74.93 are the absorption peaks of the two terminal Cs, while δ60.25 is the absorption peak of the C linked to the amide bond on the skeleton. The characteristic absorption peak of -C(=O)-O in acylated chitosan appears at δ178.38 and 178.35ppm, the absorption peak of the amide bond -C(=O)-N appears at 174.61 and 174.59ppm, and δ43.76 is the absorption peak of CH2 on the carboxylic acid.
[0053] Example 2: Preparation of carboxymethyl konjac glucomannan (CKGM):
[0054] 1) Irradiation degradation of KGM
[0055] 5 g of KGM powder was dissolved in 500 mL of 1% hydrogen peroxide solution, mixed and irradiated (60Co, Guizhou Jinnong Irradiation Technology Co., Ltd.) at doses of 2, 4, 6, 8, and 10 kGy, then concentrated by rotary evaporation until viscous, washed with anhydrous ethanol, precipitated, and freeze-dried. KGMs with different irradiation doses were named KGM2, KGM4, KGM6, KGM8, and KGM10.
[0056] The examples of this application study a method for degrading the molecular weight of KGM by using H2O2 in combination with irradiation. Irradiation degradation is caused by the free radicals generated by gamma rays randomly initiating the breakage of β-1,4 glycosidic bonds. The introduction of H2O2 is conducive to the formation of OH· free radicals, thereby improving the degradation effect. Due to the network structure formed by the interaction of molecular chains, KGM forms a relatively viscous gel state in water, showing an extremely high viscosity. Before irradiation, the apparent viscosity of KGM was 113804.38 mPa·s, and after irradiation, the apparent viscosity of KGM2 dropped to 4.38 mPa·s. As the irradiation dose increased, the apparent viscosity further decreased, and the apparent viscosities of KGM8 and KGM10 dropped to 1.04 and 1.03 mPa·s, which are close to the apparent viscosity of water.
[0057] The molecular weight trend is consistent with the apparent viscosity trend. Figure 4 As shown in the figure, the number average molecular weight (Mn), weight average molecular weight (Mw), and viscosity average molecular weight (Mz) all decreased significantly with the increase of irradiation dose. Since KGM is a chain macromolecule, its Mw is as high as 1703709Da, while the Mw of KGM2 is only 6.94% of that of KGM before irradiation, decreasing to 11827Da. With the increase of irradiation dose, Mw further decreased, and the Mw of KGM8 and KGM10 were 3635 and 1665Da, respectively, indicating that irradiation degradation caused the molecular weight of KGM to decrease sharply first and then stabilize. It is worth noting that the polydispersity index PDI was 1.15 when not irradiated, and the PDI of KGM2 and KGM4 soared to 4.87 and 2.56, respectively, after irradiation. In contrast, the PDI of higher doses (KGM6, KGM8, and KGM10) increased less after irradiation, among which KGM8 had the lowest PDI (1.79), followed by KGM6 (1.88). This indicates that the polydispersity caused by radiation degradation mainly appears after low-dose irradiation, while the molecular weight distribution is narrower under high-dose irradiation. This is related to the uniformity of irradiation. The higher the dose, the higher the irradiation uniformity.
[0058] Table 2
[0059]
[0060]
[0061] In general, the molecular weight and polydispersity of KGM decreased with increasing irradiation dose. However, under high-dose irradiation, the molecular weight distribution became more uniform, which provided useful information for the preparation of nanoparticles in the next step.
[0062] 2) Preparation of carboxymethyl konjac glucomannan (CKGM)
[0063] Take 5.0g of freeze-dried KGM2, KGM4, KGM6, KGM8, and KGM10 respectively, place them in 500mL of 70% ethanol solution, adjust the pH to 11 with 1.0mol / L NaOH solution, and alkalize for 2h. After alkalization, add 3.75g of chloroacetic acid respectively, stir with magnetic stirring in a 50℃ water bath for etherification for 3h, and then adjust the pH to 7.0 with 1.0mol / L NaOH solution. The obtained product is precipitated with 70% ethanol aqueous solution and washed with 95% ethanol aqueous solution until no residual chloride is detected in the filtrate. The precipitate is collected and dried at 50℃ until the weight is constant, and the obtained carboxymethyl konjac glucomannan is named CKGM2, CKGM4, CKGM6, CKGM8, and CKGM10.
[0064] Among them, in the preliminary experimental process, only the addition amount of chloroacetic acid was adjusted to 1.25, 2.5, 3.75, 5, 7.5, and 10 g (i.e., the mass ratio of chloroacetic acid to KGM was 0.25:1, 0.5:1, 0.75:1, 1:1, 1.5:1, and 2:1) for experiments. Combined with the characterization test, it was determined that when the mass ratio of chloroacetic acid to KGM was 0.75:1, 1:1, 1.5:1, and 2:1, the molecular weight distribution of the corresponding carboxymethyl konjac glucomannan was more concentrated, the PDI index was smaller, and the molecular weight was lower. When the mass ratio of chloroacetic acid to KGM was 0.75:1, the molecular weight distribution of the corresponding carboxymethyl konjac glucomannan was the most concentrated, the PDI index was the smallest, and the molecular weight was the lowest.
[0065] KGM is composed of mannose (M) and glucose (G) linked by β-(1,4) glycosidic bonds, with a molar ratio of M:G of 1.5: 1. It is estimated that one branch chain appears for every 10 to 11 hexose units in the main chain, and the degree of acetylation (DA) is 5 to 10%. Figure 4 A is the FT-IR spectrum of KGM and its degradation products. The spectrum between each irradiation dose group and KGM does not change much in the range of 2 to 10 kGy, indicating that its chemical structure remains relatively stable within this range. -1 The broad peak at 2901 cm -1 The absorption peak at 1730cm_1 is related to the stretching of the carbonyl group (C=O). Its absorption intensity increases slightly after irradiation, which may be due to the cleavage of the glycosidic bond caused by irradiation and H2O2 treatment, and the change of the terminal residue structure, forming a new carboxyl or carbonyl group. -1 The absorption peak is the CO stretching vibration of the hydroxyl group, 873 cm -1 and 806cm -1 It is the characteristic absorption peak of pyranose.
[0066] This application only compares the FT-IR spectra of KGM6 before and after carboxymethylation modification ( Figure 4 B) The results showed that CKGM6 at 1730cm -1 The absorption peak at 1634cm -1 The absorption peak at 40° is enhanced, which is the characteristic of asymmetric and symmetric stretching vibration of carboxyl group, indicating that carboxyl group has been successfully introduced. 1 H spectrum ( Figure 4 C), multiple NMR absorption peaks in the range of 4≤δ≤6ppm mainly represent the absorption peaks of H atoms on the OH group, while the absorption peaks in the range of 3≤δ≤4ppm are mainly related to the H atoms in the molecular skeleton, among which the peak at δ3.32 corresponds to H2. The absorption peak at δ2.15ppm indicates the presence of acetyl group, which is related to the CH asymmetric stretching vibration of CH3 group. Different from KGM, a new absorption peak was observed in CKGM6 at δ1.87ppm, representing the CH bond vibration of the methylene group on the introduced carboxyl group.
[0067] 13 C spectrum ( Figure 4 D) shows that the peak at 102.66ppm is the characteristic signal caused by the resonance of sugar ring C1, the peak at δ60.67ppm is the resonance of the side methylene carbon of C6, and the absorption peaks in the range of δ100-70ppm correspond to the remaining carbon atoms in the KGM skeleton. The CH vibration of the acetyl group is observed at δ20.72ppm. The absorption peaks at δ166.40, δ57.44, and δ16.85ppm are all produced after carboxylation, which are COO - Stretching and vibration with two methylene CH2.
[0068] Example 3: Preparation of Konjac Glucomannan-based Nanogel
[0069] A certain amount of CKGM (CKGM2, CKGM4, CKGM6, CKGM8, CKGM10 prepared in Example 2) was dissolved in MES buffer (pH 5.5) and ensured to be fully swollen to prepare a 10 mg / mL CKGM solution. EDC and NHS were added to the CKGM solution at 10 mmol / L and mixed. Then, 10 mg / mL ACs aqueous solution (prepared in Example 1) was prepared. L ACs) were added dropwise to the CKGM solution under magnetic stirring at 200 rpm, with a volume ratio of CKGM to ACs of 1:1 and a reaction time of 1 h to obtain samples, which were named L-2, L-4, L-6, L-8, and L-10.
[0070] The present invention uses the acylated chitosan with the smallest molecular weight ( L ACs) were used as the matrix and combined with CKGM of different molecular weights to prepare a series of nanogels to explore the effect of CKGM molecular weight on the particle size of nanogels. Figure 5 As shown in Figure 2, L-2 exhibited obvious aggregation, which was attributed to the larger molecular weight and higher PDI ( Figure 5 B). Larger polymer chains lead to increased entanglement, which reduces the distance between nanoparticles, thereby enhancing van der Waals forces and promoting aggregation. In addition, L-4 also showed slight aggregation, while L-6, L-8, and L-10 were not observed to aggregate. From the perspective of particle size ( Figure 5 A), the size and PDI value of L-4 are significantly higher than those of L-6, L-8, and L-10. This suggests that below a certain CKGM molecular weight, the size of the nanogel is more affected by L The influence of ACs. The size distribution of L-6, L-8, and L-10 is narrow.
[0071] Table 3
[0072] L-2 L-4 L-6 L-8 L-10 Particle size (nm) ND 427.67±12.36 346.33±7.76 366.33±7.59 326.67±45.05 PDI ND 0.3±0.13 0.11±0.07 0.18±0.06 0.08±0.06 Particle aggregation *** * - - -
[0073] Note: “***” indicates severe aggregation, “*” indicates mild aggregation, and “-” indicates no aggregation.
[0074] Example 4: Preparation of Konjac Glucomannan-based Nanogel
[0075] A certain amount of CKGM (CKGM6 prepared in Example 2) was dissolved in MES buffer (pH 5.5) and ensured to be fully swollen to prepare a 10 mg / mL CKGM solution. EDC and NHS were added to the CKGM solution at 10 mmol / L and mixed. Then, 10 mg / mL ACs aqueous solution (CKGM6 prepared in Example 1) was prepared. H ACs, M ACs and L ACs), and stir magnetically to completely dissolve them. Finally, the ACs aqueous solution was added dropwise to the CKGM6 solution under magnetic stirring at 200 rpm. The volume ratio of CKGM6 to ACs was 2:1, 1:1, and 1:2. The reaction time was 1 h to obtain samples, which were named L-6 (2:1), L-6 (1:1), L-6 (1:2), H-6 (2:1), H-6 (1:1), H-6 (1:2), M-6 (2:1), M-6 (1:1), and M-6 (1:2). The above naming rules are named according to the type and volume ratio of CKGM and ACs, such as L-2 (2:1) corresponds to L Samples with ACs:CKGM2=2:1.
[0076] Figure 5 Results from B and 5C showed that only samples H-6 (2:1), H-6 (1:2), M-6 (1:2), L-6 (1:1), and L-6 (1:2) successfully prepared konjac glucomannan-based nanogels, while the other groups showed aggregation. This indicates that when ACs dominate the system, there is a greater possibility of entanglement and aggregation, while the dominance of CKGM reduces the occurrence of aggregation.
[0077] In summary, L When ACs and CKMG6 were mixed in a volume ratio of 1:1, nanogels with smaller particle size, uniform distribution, less aggregation and the highest yield could be obtained. This conclusion is of great significance for optimizing the preparation process of nanogels and expanding their applications.
[0078] Example 5: Preparation of polyphenol nanogel
[0079] A certain amount of CKGM (CKGM6 prepared in Example 2) was dissolved in MES buffer (pH 5.5) and ensured to be fully swollen to prepare a 10 mg / mL CKGM solution. EDC and NHS were added to the CKGM solution at 10 mmol / L and mixed. RP and ACs (prepared in Example 1) were mixed with 10 mmol / L CKGM. L ACs) were mixed in a mass ratio of 1:1 in advance, and a 10 mg / mL mixed aqueous solution of ACs and RP was prepared, and magnetic stirring was performed to completely dissolve. Finally, the ACs aqueous solution was added dropwise to the CKGM6 solution under magnetic stirring at 200 rpm, the volume ratio of CKGM6 to ACs was 1:1, and the reaction time was 1 h to obtain polyphenol nanogel.
[0080] according to Figure 5 D. The color of the nanogels changed from milky white to light yellow after encapsulating polyphenols.
[0081] UV full wavelength scanning showed that the embedded nanogel showed the same strongest absorption peak as polyphenol at 280nm, which indicated that polyphenol was effectively embedded in the nanogel. As shown in the experimental data in Table 4, the embedding rate and loading rate of polyphenol reached 76.64% and 56.99% respectively, which showed that the nanogel had excellent embedding and loading capacity. In addition, the transmission electron microscopy spectrum showed that the nanogel showed an irregular shape, which may be related to the structural and morphological changes during its preparation process.
[0082] Table 4
[0083] sample L-6 L-6(loadRP) Zeta Unit (mV) 9.92±0.5 7.88±0.98 Embedding rate (%) - 0.77±0.01 Load rate (%) - 0.57±0.02
[0084] In summary, the present invention aims to prepare and characterize cross-linked carboxymethyl konjac glucomannan acylated chitosan nanogels for polyphenol encapsulation, such as Figure 6 As shown in the technical route diagram, the experiment first tested the water solubility and molecular weight of chitosan samples with different viscosities and their acylated products. Then, the molecular weight of konjac glucan was degraded by H2O2-assisted irradiation and carboxymethyl modification was performed. Two materials with more concentrated molecular weight distribution and smaller PDI index were successfully prepared: CKMG6 and L ACs. Then the effect of konjac glucan molecular weight on the particle size of nanogels was investigated. L When the volume ratio of ACs to CKGM6 was 1:1, the obtained nanogels had small particle size, uniform distribution, low aggregation tendency, and the highest yield. The prepared nanogels showed excellent polyphenol encapsulation and loading capacity. These findings provide an important reference for the optimization of the preparation process and application expansion of polysaccharide-based nanogels. Future research will focus on exploring the drug release behavior, biocompatibility, and targeted delivery applications of nanogels to further improve their efficacy and application potential in the fields of drug delivery, biomedicine, and food science.
[0085] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
[0086] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing konjac glucomannan-based nanogel, characterized in that: include: After dissolving citric acid and sodium hypophosphite in water, chitosan is added and reacted in an oil bath at 110-120° C. to obtain acylated chitosan; The konjac glucomannan is dissolved in a hydrogen peroxide solution and then subjected to irradiation degradation treatment; The konjac glucomannan treated by irradiation degradation is alkalized, and then chloroacetic acid is added for etherification to obtain carboxymethyl konjac glucomannan. The carboxymethyl konjac glucomannan is swollen in a buffer solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide are added and mixed, and then the acylated chitosan is added dropwise under stirring to react, thereby obtaining a konjac glucomannan-based nanogel; the mass ratio of the carboxymethyl konjac glucomannan to the acylated chitosan is 1:(0.5-2); In the radiation degradation treatment, the radiation dose is 6-10 kGy.
2. The method for preparing konjac glucomannan-based nanogel according to claim 1, wherein: The viscosity of the chitosan is 5-100 mPa·s.
3. The method for preparing konjac glucomannan-based nanogel according to claim 1, wherein: The weight average molecular weight of the acylated chitosan is 2500-2800Da; the weight average molecular weight of the carboxymethyl konjac glucomannan is 3000-8500Da.
4. The method for preparing konjac glucomannan-based nanogel according to claim 1, wherein: The mass ratio of the carboxymethyl konjac glucomannan to the acylated chitosan is 1:
1.
5. The method for preparing konjac glucomannan-based nanogel according to claim 1, wherein: The mass ratio of the chloroacetic acid to the konjac glucomannan is (0.75-1.5):
1.
6. The method for preparing konjac glucomannan-based nanogel according to claim 1, characterized in that: The mass ratio of the chloroacetic acid to the konjac glucomannan is 0.75:
1.
7. A konjac glucomannan-based nanogel, characterized in that: The konjac glucomannan-based nanogel is prepared by the preparation method of the konjac glucomannan-based nanogel according to any one of claims 1-6.
8. A polyphenol nanogel, characterized in that: After dissolving citric acid and sodium hypophosphite in water, chitosan is added and reacted in an oil bath at 110-120° C. to obtain acylated chitosan; after dissolving konjac glucomannan in a hydrogen peroxide solution, irradiation degradation treatment is performed; after alkalization, chloroacetic acid is added to the konjac glucomannan after irradiation degradation treatment to perform etherification treatment to obtain carboxymethyl konjac glucomannan; in the irradiation degradation treatment, the irradiation dose is 6-10 kGy; The polyphenol nanogel is prepared from carboxymethyl konjac glucomannan, acylated chitosan and polyphenol; Wherein, the mass ratio of the carboxymethyl konjac glucomannan to the acylated chitosan is 1:(0.5-2); the mass ratio of the polyphenol to the acylated chitosan is (0.5-1):
1.
9. The polyphenol nanogel according to claim 8, characterized in that: The polyphenol nanogel is prepared by swelling the carboxymethyl konjac glucomannan in a buffer solution, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to mix well, and then dropping the mixture of polyphenol and acylated chitosan under stirring to react.
Citation Information
Patent Citations
Bone tissue engineering composite porous scaffold material and preparation method thereof
CN104001211A
Method for preparing lead adsorption material
CN106000333A